Internationalization in higher education: issues facing stakeholders with possible solutions - Hansen-Devaux, Elizabeth (Kansas State University, 2011)
With more international students coming to study in the institutions of higher education in the United States, it is essential to examine the infrastructure, support system, and cross-cultural awareness which currently exist within the campus community. Issues regarding internationalization face many institutions on both the micro and macro-level due to numerous variables including the lack of communication between departments, organizations, and offices on campus and an unguided direction of the goals and ambitions behind it. By looking at how the various stakeholders involved in internationalization are affected, possible solutions for academic institutions can be suggested. This report analyzes some of the ways in which the stress and workload often associated with internationalization can be alleviated in order facilitate a community which embraces diversity, and encourages mutual respect in an ever changing global society.
Keywords: Internationalization; International students; Foreign students; Globalization; English as a Second Language (0441)